Improving the physical abilities of students of the Institute of Social Engineering that are important for their future profession through the use of mini-volleyball - Maleev P.A.; Kondrashova E.D.; Martirosova T.A.; Gorbachev A.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the influence of the mini-volley game on the development of professionally important physical qualities of students at the Institute of Social Engineering. Methods and structure of the study. To determine the key professional physical qualities of students, a survey was conducted, in which 19 teachers from the Department of Physical Education and Health, as well as the Institute of Social Engineering of the Siberian State University named after M.F. Reshetnev took part. The study itself involved 30 second-year students of the ISI of the Siberian State Agrarian University named after M.F. Reshetnev. The control group (15 girls) was represented by students of the directions 44.03.01 "Pedagogical Education" and 39.03.02 "Social Work". The experimental group (EG) also consisted of 15 girls studying in the direction 45.03.02 "Linguistics". The students from the control group trained according to programs including volleyball and basketball, while the participants of the EG studied the technique and tactics of playing mini-volleyball for two semesters (36 hours in each). Results and conclusions. It has been determined that such physical qualities as coordination, reaction speed and general physical endurance are critically important for successful professional development of graduates of the Institute of Contemporary Art (ICA). The study experimentally confirmed the effectiveness of using mini-volleyball in the training process in professional and applied physical education (PAPE) to improve coordination and speed skills, which are key physical attributes for ICA students. The developers propose integrating additional classes, including elements of mini-volleyball, into the curriculum of the PPE discipline for ICA students, with a total duration of 72 hours.